Crystals of methylpyrazole-substituted pyridoimidazole compounds and their preparation
Methylpyrazole-substituted pyridoimidazole compounds in specific crystal forms effectively target FGFR and VEGFR kinases, addressing limitations in current tumor treatments by inhibiting tumor cell proliferation and angiogenesis, with promising drug development potential.
Patent Information
- Application Number
- JP2023544759
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-26
- Filing Date
- 2022-01-26
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2042-01-26
AI Technical Summary
Current treatments for tumors involving FGFR and VEGFR pathways are limited in efficacy and specificity, particularly in targeting the synergistic effects of these pathways for anti-angiogenic and tumor inhibitory effects.
Development of methylpyrazole-substituted pyridoimidazole compounds in specific crystal forms, characterized by distinct X-ray diffraction patterns, which target and inhibit FGFR and VEGFR kinases, disrupting tumor cell proliferation and angiogenesis.
The crystal forms of the compounds exhibit strong inhibitory activity against FGFR and VEGFR pathways, demonstrating significant anti-proliferative effects on tumor cells and angiogenesis, with stable pharmacokinetic properties and potential for drug development.
Smart Images

Figure 0007606624000070 
Figure 0007606624000071 
Figure 0007606624000072
Abstract
Description
[Technical field]
[0001] The present invention relates to crystals of methylpyrazole-substituted pyridoimidazole compounds and a method for producing the same. [Background technology]
[0002] This application claims priority to the following: CN202110106007.1, application date: January 26, 2021. Fibroblast growth factor receptors (FGFRs) are a type of receptor protein that can specifically bind to fibroblast growth factors (FGFs), and the FGFRs family includes the following types: FGFR1b, FGFR1c, FGFR2b, FGFR2c, FGFR3b, FGFR3c, and FGFR4. Fibroblast growth factor receptors (FGFRs) are a type of bioactive substance that has the function of transmitting biological signals, regulating cell proliferation, and participating in tissue repair. It has been clinically discovered that abnormalities such as high expression, mutation, and fusion of FGFRs can cause the development and progression of tumors, such as liver cancer, bladder cancer, lung cancer, and breast cancer. FGFRs bind to the ligand FGF, and multiple tyrosine residues in the cell are autophosphorylated, and downstream signals are transmitted, including MEK / MAPK, PLCy / PKC, PI3K / AKT, and STATS. Therefore, FGFRs are considered to be important anti-tumor targets.
[0003] The VEGFR family includes three specific tyrosine kinase receptors: VEGFR-1, VEGFR-2 (KDR) and VEGFR-3. VEGFR-2 is an important regulator of VEGF signal transduction, which induces endothelial cell proliferation, enhances vascular permeability and promotes angiogenesis, and the affinity between VEGFR-2 and VEGF is higher than that of VEGFR-1. Studies have shown that only VEGFR-2 is expressed in endothelial cells, and activation of VEGFR-2 can efficiently stimulate angiogenesis. Therefore, VEGFR-2 is the main target for the development of antiangiogenic drugs.
[0004] The VEGFR and FGFR pathways cooperate to complete the activation and generation of endothelial cells in angiogenesis, and VEGF may require the presence of FGF to exert its pro-angiogenic effect. The synergistic effect of the FGFR and VEGFR pathways can also inhibit tumor immune evasion and enhance tumor inhibitory effects. Summary of the Invention [Means for solving the problem]
[0005] The present invention provides a compound represented by formula (II): [ka]
[0006] The present invention provides a type A crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.65±0.20°, 17.70±0.20°, and 24.02±0.20°.
[0007] [ka]
[0008] In some embodiments of the present invention, the powder X-ray diffraction pattern of the A-type crystals has characteristic diffraction peaks at the following 2θ angles: 7.65±0.20°, 16.84±0.20°, 17.70±0.20°, 20.10±0.20°, 20.91±0.20°, and 24.02±0.20°.
[0009] In some embodiments of the present invention, the powder X-ray diffraction pattern of the A-type crystals has characteristic diffraction peaks at the following 2θ angles: 7.65±0.20°, 16.84±0.20°, 17.70±0.20°, 20.10±0.20°, 20.91±0.20°, 24.02±0.20°, 24.98±0.20°, and 26.60±0.20°.
[0010] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Form A crystals has characteristic diffraction peaks at the following 2θ angles: 7.65±0.20°, 17.70±0.20°, and / or 24.02±0.20°, and / or 16.84±0.20°, and / or 20.10±0.20°, and / or 20.91±0.20°, and / or 24.98±0.20°, and / or 26.60±0.20°, and / or 12.71±0.20°, and / or 28.08±0.20°.
[0011] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Form A crystal has characteristic diffraction peaks at the following 2θ angles: 7.649°, 12.713°, 16.841°, 17.695°, 20.100°, 20.912°, 24.018°, 24.976°, 26.599°, and 28.076°.
[0012] In some embodiments of the present invention, the XRPD pattern of the Form A crystals is as shown in FIG.
[0013] In some embodiments of the present invention, the analytical data of the XRPD pattern of the A-type crystal is as shown in Table 1.
[0014] [Table 1]
[0015] In some embodiments of the present invention, the differential scanning calorimetry curve of the A-type crystals exhibits one endothermic peak value at 283.9±3.0°C.
[0016] In some embodiments of the present invention, the DSC pattern of the A-type crystals is as shown in FIG.
[0017] In some embodiments of the present invention, the thermogravimetric analysis curve of the A-type crystals shows a weight loss of 0.955% at 200.0±3.0°C.
[0018] In some embodiments of the present invention, the TGA pattern of the Form A crystals is as shown in FIG.
[0019] The present invention provides a B-type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.75±0.20°, 9.94±0.20°, and 23.94±0.20°.
[0020] [ka]
[0021] In some embodiments of the present invention, the powder X-ray diffraction pattern of the B-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.75±0.20°, 9.94±0.20°, 11.70±0.20°, 17.52±0.20°, 20.36±0.20°, and 23.94±0.20°.
[0022] In some embodiments of the present invention, the powder X-ray diffraction pattern of the B-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.75±0.20°, 9.94±0.20°, 11.70±0.20°, 14.38±0.20°, 17.52±0.20°, 18.95±0.20°, 20.36±0.20°, and 23.94±0.20°.
[0023] In some embodiments of the present invention, the powder X-ray diffraction pattern of the B-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.75°, 9.94°, 11.70°, 13.62°, 14.38°, 15.47°, 17.52°, 18.95°, 20.36°, 23.94°, 25.34°, 25.46°, 26.93°, and 28.79°.
[0024] In some embodiments of the present invention, the XRPD pattern of the B-type crystals is as shown in FIG.
[0025] In some embodiments of the present invention, the analytical data of the XRPD pattern of the B-type crystal is as shown in Table 2.
[0026] [Table 2]
[0027] In some embodiments of the present invention, the differential scanning calorimetry curve of the B-type crystals shows the onset of one endothermic peak at 57.40±3.0° C. and 296.86±3.0° C., respectively.
[0028] In some embodiments of the present invention, the DSC pattern of the B-type crystals is as shown in FIG.
[0029] In some embodiments of the present invention, the thermogravimetric analysis curve of the B-type crystals shows a weight loss of 10.53% at 150.0±3.0°C.
[0030] In some embodiments of the present invention, the TGA pattern of the B-type crystals is as shown in FIG.
[0031] The present invention provides a C-type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 10.74±0.20°, 13.64±0.20°, and 21.14±0.20°.
[0032] [ka]
[0033] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 10.74±0.20°, 13.64±0.20°, 19.62±0.20°, 21.14±0.20°, 25.45±0.20°, and 25.96±0.20°.
[0034] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 8.70±0.20°, 10.74±0.20°, 13.64±0.20°, 16.63±0.20°, 19.62±0.20°, 21.14±0.20°, 25.45±0.20°, and 27.47±0.20°.
[0035] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.44°, 8.70°, 10.74°, 13.64°, 15.85°, 16.63°, 17.44°, 19.62°, 21.14°, 21.61°, 24.26°, 25.45°, 25.96°, 27.47°, and 29.07°.
[0036] In some embodiments of the present invention, the XRPD pattern of the C-type crystals is as shown in FIG.
[0037] In some embodiments of the present invention, the analytical data of the XRPD pattern of the C-type crystal is as shown in Table 3.
[0038] [Table 3]
[0039] In some embodiments of the present invention, the differential scanning calorimetry curve of the C-type crystals shows the onset of one endothermic peak at 37.60±3.0° C. and 299.00±3.0° C., respectively.
[0040] In some embodiments of the present invention, the DSC pattern of the C-type crystals is as shown in FIG.
[0041] In some embodiments of the present invention, the thermogravimetric analysis curve of the C-type crystals shows a weight loss of 7.91% at 150.0±3.0°C.
[0042] In some embodiments of the present invention, the TGA pattern of the C-type crystals is as shown in FIG.
[0043] The present invention provides a D-type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 10.78±0.20°, 13.64±0.20°, and 16.66±0.20°.
[0044] [ka]
[0045] In some embodiments of the present invention, the powder X-ray diffraction pattern of the D-type crystals has characteristic diffraction peaks at the following 2θ angles: 10.78±0.20°, 13.64±0.20°, 16.66±0.20°, 19.63±0.20°, 21.13±0.20°, and 25.40±0.20°.
[0046] In some embodiments of the present invention, the powder X-ray diffraction pattern of the D-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.51±0.20°, 8.73±0.20°, 10.78±0.20°, 13.64±0.20°, 16.66±0.20°, 19.63±0.20°, 21.13±0.20°, and 25.40±0.20°.
[0047] In some embodiments of the present invention, the powder X-ray diffraction pattern of the D-type crystals is at the following 2θ angles: 5.51°, 8.10°, 8.73°, 10.78°, 12.64°, 13.64°, 14.47°, 14.92°, 15.80°, 16.66°, 17.47°, 19.03°, 19.63°, 21.13°, and 21. It has characteristic diffraction peaks at 69°, 22.02°, 22.20°, 23.84°, 24.31°, 25.40°, 25.93°, 26.28°, 26.84°, 27.41°, 27.93°, 29.10°, 30.01°, 30.78°, 32.16°, 32.78°, 33.57°, and 38.41°.
[0048] In some embodiments of the present invention, the XRPD pattern of the Form D crystal is as shown in FIG.
[0049] In some embodiments of the present invention, the analytical data of the XRPD pattern of the D-type crystal is as shown in Table 4.
[0050] [Table 4]
[0051] In some embodiments of the present invention, the differential scanning calorimetry curve of the D-type crystals shows the onset of one endothermic peak at 27.1±3.0° C. and 298.8±3.0° C., respectively.
[0052] In some embodiments of the present invention, the DSC pattern of the D-type crystal is as shown in FIG.
[0053] In some embodiments of the present invention, the thermogravimetric analysis curve of the D-type crystals shows a weight loss of 3.15% at 150.0±3.0°C.
[0054] In some embodiments of the present invention, the TGA pattern of the D-type crystals is as shown in FIG.
[0055] The present invention provides a compound represented by formula (III):
[0056] [ka]
[0057] The present invention provides type E crystals of the compound represented by formula (III), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 9.56±0.20°, 19.10±0.20°, and 27.12±0.20°.
[0058] [ka]
[0059] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.56±0.20°, 10.82±0.20°, 16.94±0.20°, 19.10±0.20°, 27.12±0.20°, and 28.76±0.20°.
[0060] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.56±0.20°, 10.82±0.20°, 16.94±0.20°, 17.57±0.20°, 19.10±0.20°, 25.00±0.20°, 27.12±0.20°, and 28.76±0.20°.
[0061] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystals has characteristic diffraction peaks at the following 2θ angles: 7.01°, 9.56°, 10.82°, 13.51°, 13.97°, 16.94°, 17.57°, 19.10°, 21.26°, 23.73°, 24.47°, 25.00°, 26.04°, 26.62°, 27.12°, 28.33°, 28.76°, 29.22°, 30.59°, 31.56°, 32.72°, 35.31°, 36.10°, 37.25°, and 38.64°.
[0062] In some embodiments of the present invention, the XRPD pattern of the Form E crystals is as shown in FIG.
[0063] In some embodiments of the present invention, the analytical data of the XRPD pattern of the E-type crystal is as shown in Table 5.
[0064] [Table 5]
[0065] In some embodiments of the present invention, the differential scanning calorimetry curve of the E-type crystals shows an endothermic peak at 303.8±3.0° C.
[0066] In some embodiments of the present invention, the DSC pattern of the E-type crystal is as shown in FIG.
[0067] In some embodiments of the present invention, the thermogravimetric analysis curve of the E-type crystals shows a weight loss of 2.27% at 200.0±3.0°C.
[0068] In some embodiments of the present invention, the TGA pattern of the E-type crystals is as shown in FIG.
[0069] The present invention provides an F-type crystal of the compound represented by formula (III), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 8.08±0.20°, 19.09±0.20°, and 26.87±0.20°.
[0070] [ka]
[0071] In some embodiments of the present invention, the powder X-ray diffraction pattern of the F-type crystals has characteristic diffraction peaks at the following 2θ angles: 8.08±0.20°, 9.51±0.20°, 12.40±0.20°, 19.09±0.20°, 24.91±0.20°, and 26.87±0.20°.
[0072] In some embodiments of the present invention, the powder X-ray diffraction pattern of the F-type crystals has characteristic diffraction peaks at the following 2θ angles: 8.08±0.20°, 9.51±0.20°, 12.40±0.20°, 16.80±0.20°, 17.70±0.20°, 19.09±0.20°, 24.91±0.20°, and 26.87±0.20°.
[0073] In some embodiments of the present invention, the powder X-ray diffraction pattern of the F-type crystals has characteristic diffraction peaks at the following 2θ angles: 8.08°, 9.51°, 12.40°, 13.34°, 14.53°, 16.80°, 17.70°, 19.09°, 20.34°, 22.34°, 24.91°, 26.87°, and 28.87°.
[0074] In some embodiments of the present invention, the XRPD pattern of the F-type crystals is as shown in FIG.
[0075] In some embodiments of the present invention, the analytical data of the XRPD pattern of the F-type crystal is as shown in Table 6.
[0076] [Table 6]
[0077] The present invention provides a G-type crystal of the compound represented by formula (III), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 8.79±0.20°, 17.53±0.20°, and 26.33±0.20°.
[0078] [ka]
[0079] In some embodiments of the present invention, the powder X-ray diffraction pattern of the G-type crystal has characteristic diffraction peaks at the following 2θ angles: 8.79±0.20°, 12.34±0.20°, 17.53±0.20°, 19.10±0.20°, 25.16±0.20°, and 26.33±0.20°.
[0080] In some embodiments of the present invention, the powder X-ray diffraction pattern of the G-type crystal has characteristic diffraction peaks at the following 2θ angles: 8.79±0.20°, 12.34±0.20°, 17.53±0.20°, 19.10±0.20°, 19.65±0.20°, 21.45±0.20°, 25.16±0.20°, and 26.33±0.20°.
[0081] In some embodiments of the present invention, the powder X-ray diffraction pattern of the G-type crystal has characteristic diffraction peaks at the following 2θ angles: 8.79°, 12.34°, 13.92°, 15.13°, 15.76°, 17.08°, 17.53°, 19.10°, 19.65°, 20.61°, 21.45°, 21.90°, 23.38°, 25.16°, 26.33°, 26.70°, 29.18°, 35.42°, and 37.62°.
[0082] In some embodiments of the present invention, the XRPD pattern of the G-type crystal is as shown in FIG.
[0083] In some embodiments of the present invention, the analytical data of the XRPD pattern of the G-type crystal is as shown in Table 7.
[0084] [Table 7]
[0085] The present invention provides a compound represented by formula (IV):
[0086] [ka]
[0087] The present invention provides an H-type crystal of the compound represented by formula (IV), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.65±0.20°, 17.80±0.20°, and 18.92±0.20°.
[0088] [ka]
[0089] In some embodiments of the present invention, the powder X-ray diffraction pattern of the H-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.65±0.20°, 13.42±0.20°, 17.80±0.20°, 18.92±0.20°, 21.99±0.20°, and 24.42±0.20°.
[0090] In some embodiments of the present invention, the powder X-ray diffraction pattern of the H-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.65±0.20°, 13.42±0.20°, 17.80±0.20°, 18.92±0.20°, 20.05±0.20°, 21.99±0.20°, 24.42±0.20°, and 26.30±0.20°.
[0091] In some embodiments of the present invention, the powder X-ray diffraction pattern of the H-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.65°, 13.42°, 17.80°, 18.45°, 18.92°, 20.05°, 21.99°, 24.42°, 26.30°, and 27.00°.
[0092] In some embodiments of the present invention, the XRPD pattern of the H-form crystals is as shown in FIG.
[0093] In some embodiments of the present invention, the analytical data of the XRPD pattern of the H-type crystal is as shown in Table 8.
[0094] [Table 8]
[0095] In some embodiments of the present invention, the differential scanning calorimetry curve of the H-type crystals shows the onset of one endothermic peak at 275.73±3.0° C. and 310.54±3.0° C., respectively.
[0096] In some embodiments of the present invention, the DSC pattern of the H-type crystals is as shown in FIG.
[0097] In some embodiments of the present invention, the thermogravimetric analysis curve of the H-type crystals shows a weight loss of 8.58% at 200.0±3.0°C and a weight loss of 2.45% at 260.0±3.0°C.
[0098] In some embodiments of the present invention, the TGA pattern of the H-type crystals is as shown in FIG.
[0099] The present invention provides a type I crystal of the compound represented by formula (IV), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 5.33±0.20°, 13.74±0.20°, and 20.66±0.20°.
[0100] [ka]
[0101] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Form I crystal has characteristic diffraction peaks at the following 2θ angles: 5.33±0.20°, 9.02±0.20°, 13.74±0.20°, 18.16±0.20°, 20.66±0.20°, and 21.91±0.20°.
[0102] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Form I crystal has characteristic diffraction peaks at the following 2θ angles: 5.33±0.20°, 9.02±0.20°, 11.77±0.20°, 13.74±0.20°, 17.51±0.20°, 18.16±0.20°, 20.66±0.20°, and 21.91±0.20°.
[0103] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Form I crystal has characteristic diffraction peaks at the following 2θ angles: 5.33°, 9.02°, 10.62°, 11.77°, 13.74°, 15.99°, 17.51°, 18.16°, 19.63°, 20.66°, 21.24°, 21.91°, 23.15°, 24.94°, and 26.89°.
[0104] In some embodiments of the present invention, the XRPD pattern of the Form I crystal is as shown in FIG.
[0105] In some embodiments of the present invention, the analytical data of the XRPD pattern of the above Form I crystal is as shown in Table 9.
[0106] [Table 9]
[0107] The present invention provides a J-type crystal of the compound represented by formula (IV), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 5.24±0.20°, 18.48±0.20°, and 20.79±0.20°.
[0108] [ka]
[0109] In some embodiments of the present invention, the powder X-ray diffraction pattern of the J-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.24±0.20°, 18.48±0.20°, 19.77±0.20°, 20.79±0.20°, 22.67±0.20°, and 23.24±0.20°.
[0110] In some embodiments of the present invention, the powder X-ray diffraction pattern of the J-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.24±0.20°, 18.48±0.20°, 19.77±0.20°, 20.79±0.20°, 22.67±0.20°, 23.24±0.20°, 24.20±0.20°, and 26.28±0.20°.
[0111] In some embodiments of the present invention, the powder X-ray diffraction pattern of the J-type crystal has characteristic diffraction peaks at the following 2θ angles: 5.24°, 12.55°, 13.78°, 14.86°, 16.30°, 17.19°, 18.48°, 19.77°, 20.79°, 22.67°, 23.24°, 24.20°, and 26.28°.
[0112] In some embodiments of the present invention, the XRPD pattern of the J-type crystals is as shown in FIG.
[0113] In some embodiments of the present invention, the analytical data of the XRPD pattern of the J-type crystal is as shown in Table 10.
[0114] [Table 10]
[0115] The present invention provides a K-type crystal of the compound represented by formula (IV), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 17.97±0.20°, 20.47±0.20°, and 25.16±0.20°.
[0116] [ka]
[0117] In some embodiments of the present invention, the powder X-ray diffraction pattern of the K-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.79±0.20°, 17.97±0.20°, 20.47±0.20°, 23.46±0.20°, 23.87±0.20°, and 25.16±0.20°.
[0118] In some embodiments of the present invention, the powder X-ray diffraction pattern of the K-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.79±0.20°, 17.97±0.20°, 18.74±0.20°, 19.47±0.20°, 20.47±0.20°, 23.46±0.20°, 23.87±0.20°, and 25.16±0.20°.
[0119] In some embodiments of the present invention, the powder X-ray diffraction pattern of the K-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.79°, 7.87°, 8.65°, 11.69°, 16.47°, 17.97°, 18.28°, 18.74°, 19.47°, 20.47°, 20.76°, 21.73°, 22.33°, 23.46°, 23.87°, 25.16°, 25.94°, 26.30°, 27.06°, 28.07°, 29.34°, 30.18°, 31.69°, 33.26°, and 34.45°.
[0120] In some embodiments of the present invention, the XRPD pattern of the K-type crystals is as shown in FIG.
[0121] In some embodiments of the present invention, the analytical data of the XRPD pattern of the K-type crystal is as shown in Table 11.
[0122] [Table 11]
[0123] The present invention provides a compound represented by formula (V):
[0124] [ka]
[0125] The present invention provides an L-type crystal of the compound represented by formula (V), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 5.85±0.20°, 16.75±0.20°, and 20.67±0.20°.
[0126] [ka]
[0127] In some embodiments of the present invention, the powder X-ray diffraction pattern of the L-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.85±0.20°, 11.57±0.20°, 16.75±0.20°, 20.67±0.20°, 22.50±0.20°, and 25.29±0.20°.
[0128] In some embodiments of the present invention, the powder X-ray diffraction pattern of the L-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.85±0.20°, 11.57±0.20°, 16.75±0.20°, 18.10±0.20°, 20.67±0.20°, 22.50±0.20°, 23.34±0.20°, and 25.29±0.20°.
[0129] In some embodiments of the present invention, the powder X-ray diffraction pattern of the L-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.85°, 8.36°, 11.57°, 16.75°, 18.10°, 20.67°, 22.50°, 23.34°, 25.29°, 27.93°, and 31.76°.
[0130] In some embodiments of the present invention, the XRPD pattern of the Form L crystals is as shown in FIG.
[0131] In some embodiments of the present invention, the analytical data of the XRPD pattern of the above-mentioned Form L crystal is as shown in Table 12.
[0132] [Table 12]
[0133] The present invention provides an M-type crystal of the compound represented by formula (V), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 5.72±0.20°, 16.77±0.20°, and 17.51±0.20°.
[0134] [ka]
[0135] In some embodiments of the present invention, the powder X-ray diffraction pattern of the M-type crystal has characteristic diffraction peaks at the following 2θ angles: 5.72±0.20°, 11.52±0.20°, 16.77±0.20°, 17.51±0.20°, 18.10±0.20°, and 20.05±0.20°.
[0136] In some embodiments of the present invention, the powder X-ray diffraction pattern of the M-type crystal has characteristic diffraction peaks at the following 2θ angles: 5.72±0.20°, 11.52±0.20°, 16.77±0.20°, 17.51±0.20°, 18.10±0.20°, 20.05±0.20°, 22.48±0.20°, and 25.30±0.20°.
[0137] In some embodiments of the present invention, the powder X-ray diffraction pattern of the M-type crystal has characteristic diffraction peaks at the following 2θ angles: 5.42°, 5.72°, 11.52°, 13.57°, 14.92°, 16.77°, 17.51°, 18.10°, 20.05°, 22.48°, 23.35°, 23.91°, 25.30°, 27.10°, 27.94°, 30.00°, and 31.77°.
[0138] In some embodiments of the present invention, the XRPD pattern of the M-type crystals is as shown in FIG.
[0139] In some embodiments of the present invention, the analytical data of the XRPD pattern of the M-type crystal is as shown in Table 13.
[0140] [Table 13]
[0141] The present invention provides an N-type crystal of a compound represented by formula (V), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 4.55±0.20°, 16.76±0.20°, and 18.30±0.20°.
[0142] [ka]
[0143] In some embodiments of the present invention, the powder X-ray diffraction pattern of the N-type crystal has characteristic diffraction peaks at the following 2θ angles: 4.55±0.20°, 16.14±0.20°, 16.76±0.20°, 17.20±0.20°, 18.30±0.20°, and 20.22±0.20°.
[0144] In some embodiments of the present invention, the powder X-ray diffraction pattern of the N-type crystal has characteristic diffraction peaks at the following 2θ angles: 4.55±0.20°, 16.14±0.20°, 16.76±0.20°, 17.20±0.20°, 18.30±0.20°, 20.22±0.20°, 22.63±0.20°, and 24.50±0.20°.
[0145] In some embodiments of the present invention, the powder X-ray diffraction pattern of the N-type crystal has characteristic diffraction peaks at the following 2θ angles: 4.55°, 16.14°, 16.76°, 17.20°, 18.30°, 20.22°, 22.63°, 24.50°, 26.73°, and 31.76°.
[0146] In some embodiments of the present invention, the XRPD pattern of the N-type crystals is as shown in FIG.
[0147] In some embodiments of the present invention, the analytical data of the XRPD pattern of the N-type crystal is as shown in Table 14.
[0148] [Table 14]
[0149] The present invention provides a compound represented by formula (VI): [ka]
[0150] The present invention provides an O-type crystal of a compound represented by formula (VI), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 4.57±0.20°, 5.79±0.20°, and 18.06±0.20°.
[0151] [ka]
[0152] In some embodiments of the present invention, the powder X-ray diffraction pattern of the O-type crystals has characteristic diffraction peaks at the following 2θ angles: 4.57±0.20°, 5.79±0.20°, 16.38±0.20°, 18.06±0.20°, 19.32±0.20°, and 20.13±0.20°.
[0153] In some embodiments of the present invention, the powder X-ray diffraction pattern of the O-type crystals has characteristic diffraction peaks at the following 2θ angles: 4.57±0.20°, 5.79±0.20°, 9.09±0.20°, 14.52±0.20°, 16.38±0.20°, 18.06±0.20°, 19.32±0.20°, and 20.13±0.20°.
[0154] In some embodiments of the present invention, the powder X-ray diffraction pattern of the O-type crystals has characteristic diffraction peaks at the following 2θ angles: 4.57°, 5.79°, 6.45°, 9.09°, 10.09°, 12.20°, 13.04°, 14.52°, 16.38°, 18.06°, 18.33°, 19.32°, 20.13°, 22.42°, 22.74°, 23.32°, 23.90°, 27.37°, and 29.29°.
[0155] In some embodiments of the present invention, the XRPD pattern of the O-type crystals is as shown in FIG.
[0156] In some embodiments of the present invention, the analytical data of the XRPD pattern of the O-type crystals is as shown in Table 15.
[0157] [Table 15]
[0158] The present invention provides a P-type crystal of the compound represented by formula (VI), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 9.96±0.20°, 17.02±0.20°, and 21.78±0.20°.
[0159] [ka]
[0160] In some embodiments of the present invention, the powder X-ray diffraction pattern of the P-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.96±0.20°, 17.02±0.20°, 21.31±0.20°, 21.78±0.20°, 24.71±0.20°, and 25.52±0.20°.
[0161] In some embodiments of the present invention, the powder X-ray diffraction pattern of the P-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.96±0.20°, 16.23±0.20°, 17.02±0.20°, 17.81±0.20°, 21.31±0.20°, 21.78±0.20°, 24.71±0.20°, and 25.52±0.20°.
[0162] In some embodiments of the present invention, the powder X-ray diffraction pattern of the P-type crystals has characteristic diffraction peaks at the following 2θ angles: 6.87°, 8.26°, 9.96°, 13.64°, 15.18°, 16.23°, 17.02°, 17.81°, 18.62°, 21.31°, 21.78°, 24.71°, 25.52°, 29.14°, and 31.47°.
[0163] In some embodiments of the present invention, the XRPD pattern of the P-type crystals is as shown in FIG.
[0164] In some embodiments of the present invention, the analytical data of the XRPD pattern of the P-type crystal is as shown in Table 16.
[0165] [Table 16]
[0166] The present invention provides a compound represented by formula (VII): [ka]
[0167] The present invention provides a Q-type crystal of the compound represented by formula (VII), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.90±0.20°, 16.76±0.20°, and 25.94±0.20°.
[0168] [ka]
[0169] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Q-type crystals has characteristic diffraction peaks at the following 2θ angles: 7.90±0.20°, 16.76±0.20°, 17.19±0.20°, 20.09±0.20°, 23.82±0.20°, and 25.94±0.20°.
[0170] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Q-type crystals has characteristic diffraction peaks at the following 2θ angles: 7.90±0.20°, 11.53±0.20°, 16.76±0.20°, 17.19±0.20°, 20.09±0.20°, 20.94±0.20°, 23.82±0.20°, and 25.94±0.20°.
[0171] In some embodiments of the present invention, the powder X-ray diffraction pattern of the Q-type crystals has characteristic diffraction peaks at the following 2θ angles: 7.90°, 8.53°, 9.90°, 11.53°, 12.98°, 15.12°, 16.76°, 17.19°, 19.68°, 20.09°, 20.94°, 22.50°, 22.86°, 23.82°, 25.32°, 25.94°, 27.16°, 27.83°, 29.17°, 30.11°, 31.83°, and 33.48°.
[0172] In some embodiments of the present invention, the XRPD pattern of the Type Q crystals is as shown in FIG.
[0173] In some embodiments of the present invention, the analytical data of the XRPD pattern of the Q-type crystal is as shown in Table 17.
[0174] [Table 17]
[0175] The present invention provides a compound represented by formula (VIII):
[0176] [ka]
[0177] The present invention provides an R-type crystal of the compound represented by formula (VIII), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 3.18±0.20°, 6.43±0.20°, and 16.67±0.20°.
[0178] [ka]
[0179] In some embodiments of the present invention, the powder X-ray diffraction pattern of the R-type crystal has characteristic diffraction peaks at the following 2θ angles: 3.18±0.20°, 6.43±0.20°, 16.67±0.20°, 18.20±0.20°, 18.63±0.20°, and 19.53±0.20°.
[0180] In some embodiments of the present invention, the powder X-ray diffraction pattern of the R-type crystal has characteristic diffraction peaks at the following 2θ angles: 3.18±0.20°, 6.43±0.20°, 16.67±0.20°, 18.20±0.20°, 18.63±0.20°, 19.53±0.20°, 20.02±0.20°, and 27.78±0.20°.
[0181] In some embodiments of the present invention, the powder X-ray diffraction pattern of the R-type crystal has characteristic diffraction peaks at the following 2θ angles: 3.18°, 6.43°, 11.35°, 13.24°, 16.67°, 18.20°, 18.63°, 19.53°, 20.02°, 21.59°, 23.44°, and 27.78°.
[0182] In some embodiments of the present invention, the XRPD pattern of the R-type crystals is as shown in FIG.
[0183] In some embodiments of the present invention, the analytical data of the XRPD pattern of the R-type crystal is as shown in Table 18.
[0184] [Table 18]
[0185] The present invention provides a compound represented by formula (X):
[0186] [ka]
[0187] The present invention provides an S-type crystal of the compound represented by formula (X), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 4.74±0.20°, 17.04±0.20°, and 24.77±0.20°.
[0188] [ka]
[0189] In some embodiments of the present invention, the powder X-ray diffraction pattern of the S-type crystal has characteristic diffraction peaks at the following 2θ angles: 4.74±0.20°, 11.97±0.20°, 17.04±0.20°, 20.65±0.20°, 24.77±0.20°, and 31.75±0.20°.
[0190] In some embodiments of the present invention, the XRPD pattern of the S-form crystal is as shown in FIG.
[0191] In some embodiments of the present invention, the analytical data of the XRPD pattern of the S-type crystal is as shown in Table 19.
[0192] [Table 19]
[0193] The present invention provides a T-type crystal of the compound represented by formula (I), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 8.37±0.20°, 11.54±0.20°, and 16.76±0.20°.
[0194] [ka]
[0195] In some embodiments of the present invention, the powder X-ray diffraction pattern of the T-type crystals has characteristic diffraction peaks at the following 2θ angles: 8.37±0.20°, 11.54±0.20°, 16.76±0.20°, 22.49±0.20°, 23.36±0.20°, and 25.26±0.20°.
[0196] In some embodiments of the present invention, the powder X-ray diffraction pattern of the T-type crystals has characteristic diffraction peaks at the following 2θ angles: 8.37±0.20°, 11.54±0.20°, 16.76±0.20°, 19.53±0.20°, 22.49±0.20°, 23.36±0.20°, 25.26±0.20°, and 27.12±0.20°.
[0197] In some embodiments of the present invention, the powder X-ray diffraction pattern of the T-type crystals has characteristic diffraction peaks at the following 2θ angles: 8.37°, 9.98°, 11.54°, 13.44°, 15.08°, 16.76°, 18.70°, 19.53°, 20.03°, 21.14°, 22.49°, 23.36°, 25.26°, 27.12°, 27.92°, and 31.77°.
[0198] In some embodiments of the present invention, the XRPD pattern of the T-type crystals is as shown in FIG.
[0199] In some embodiments of the present invention, the analytical data of the XRPD pattern of the T-type crystal is as shown in Table 20.
[0200] [Table 20-1]
[0201] In some embodiments of the present invention, the differential scanning calorimetry curve of the T-type crystals shows one endothermic peak value at 282.6±3.0°C.
[0202] In some embodiments of the present invention, the DSC pattern of the T-type crystal is as shown in FIG.
[0203] In some embodiments of the present invention, the thermogravimetric analysis curve of the T-type crystals shows a weight loss of 1.56% at 250.0±3.0° C.
[0204] In some embodiments of the present invention, the TGA pattern of the T-type crystal is as shown in FIG.
[0205] The present invention further provides use of the above compound or the above Type A crystals, Type B crystals, Type C crystals, Type D crystals, Type E crystals, Type F crystals, Type G crystals, Type H crystals, Type I crystals, Type J crystals, Type K crystals, Type L crystals, Type M crystals, Type N crystals, Type O crystals, Type P crystals, Type Q crystals, Type R crystals, Type S crystals and Type T crystals in the manufacture of a medicament for treating a disease associated with an FGFR / VEGFR dikinase inhibitor.
[0206] In some embodiments of the present invention, the above-mentioned use is characterized in that the drug related to the FGFR / VEGFR dikinase inhibitor is a drug for treating a solid tumor. <Definitions and Explanations>
[0207] The following terms and phrases used herein shall have the following meanings unless otherwise stated. Certain words or terms, unless specifically defined, should not be considered indefinite or unclear but should be understood according to their ordinary meaning. When a trade name is mentioned herein, it is intended to refer to the corresponding product or its active ingredients.
[0208] The intermediate compounds of the present invention can be prepared by various synthetic methods known to those skilled in the art, including the specific embodiments listed below, embodiments formed by combination with other chemical synthetic methods, and equivalent substitution methods known to those skilled in the art, and preferred embodiments include, but are not limited to, the examples of the present invention.
[0209] The chemical reactions of certain embodiments of the present invention are completed in a suitable solvent, which should be suitable for the chemical transformations of the present invention and the reagents and materials required therefor. To obtain the compounds of the present invention, those skilled in the art may need to modify or select synthetic steps or reaction schemes based on existing embodiments.
[0210] The structure of the compound of the present invention can be confirmed by conventional methods known to those skilled in the art, and when the present invention relates to the absolute configuration of a compound, the absolute configuration can be confirmed by conventional technical means in the art.For example, single crystal X-ray diffraction method (SXRD) is to collect diffraction intensity data of cultured single crystal with Bruker D8 venture diffractometer, the light source is CuKα radiation, the scanning method is φ / ω scanning, and after collecting relevant data, the crystal structure can be further analyzed by direct method (Shelxs97) to confirm the absolute configuration.
[0211] Unless otherwise stated, the DSC patterns used herein are downward endotherms.
[0212] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way.
[0213] All of the solvents used in this invention are commercially available and can be used without further purification.
[0214] The solvent used in the present invention can be obtained from commercial products. The present invention uses the following abbreviations: DCM stands for dichloromethane, DMF stands for N,N-dimethylformamide, DMSO stands for dimethylsulfoxide, EtOH stands for ethanol, MeOH stands for methanol, TFA stands for trifluoroacetic acid, ATP stands for adenosine triphosphate, HEPES stands for 4-hydroxyethylpiperazineethanesulfonic acid, MgCl2 stands for magnesium dichloride, and Pd(PPh3)2Cl2 stands for bis(triphenylphosphine)palladium(II) dichloride. Effect of the Invention
[0215] The crystals of the compound of the present invention have good stability and can be easily formulated into medicines, and the crystals of the compound of the present invention have excellent DNA-PK kinase inhibitory activity.
[0216] Powder X-ray Diffractometer (XRPD) of the Present Invention Equipment model: PANalytical's X'Pert 3 X-ray diffractometer Test method: Approximately 10 mg of sample is used for XRPD detection.
[0217] Detailed XRPD parameters are as follows: Radiation source: Cu Kα (Kα1 = 1.540598 Å, Kα2 = 1.544426 Å, Kα2 / Kα1 intensity ratio: 0.5) Light-emitting tube voltage: 45 kV, light-emitting tube current: 40 mA Divergence slit: fixed at 1 / 8 deg First Soller slit: 0.04rad, second Soller slit: 0.04rad Receiving slit: None, Anti-scattering slit: 7.5 mm Measurement time: 5 min Scan angle range: 3~40deg Step width angle: 0.0263deg Step size: 46.665 seconds Sample tray speed: 15 rpm Differential Scanning Calorimeter (DSC) of the Present Invention Instrument model: TA Discovery DSC 2500 Differential Scanning Calorimeter Test method: Take a sample (approximately 1 to 5 mg) and place it in an aluminum pan for DSC. Heat the sample from 25°C (room temperature) to just before the sample decomposes at a heating rate of 10°C / min under 50mL / min N2 conditions.
[0218] Thermogravimetric Analysis (Thermal Gravimetric Analyzer, TGA) of the Present Invention Instrument model: TA Discovery TGA 5500 Thermogravimetric Analyzer Test method: Take a sample (approximately 1 to 5 mg) and place it in an aluminum pan for TGA. Heat the sample from room temperature to 350°C at a heating rate of 10°C / min under 10mL / min N2 conditions.
[0219] Dynamic Vapor Sorption (DVS) Method of the Present Invention Instrument model: SMS Intrinsic Dynamic Water Vapor Sorption Instrument Test conditions: Take a sample (approximately 10-30 mg) and place it in the DVS sample tray for testing.
[0220] The detailed DVS parameters are as follows: Temperature: 25℃ Balance: dm / dt=0.002% / min (min: 10min, max: 180min) RH range: 0%RH-95%RH-0%RH RH gradient: 10% (90%RH-0%RH-90%RH) 5% (95%RH-90%RH and 90%RH-95%RH)
[0221] The moisture absorption rating categories are as follows: [Table 20-2]
[0222] Note: ΔW% represents the increase in moisture weight of the test sample at 25±1℃ and 80±2% RH. [Brief description of the drawings]
[0223] [Figure 1] 1 is an XRPD pattern of Cu-Kα radiation of the A-type crystal of the compound of formula (II). [Diagram 2] 1 is a DSC pattern of the A-type crystals of the compound of formula (II). [Diagram 3] 1 is a TGA pattern of crystal form A of the compound of formula (II). [Figure 4] 1 is an XRPD pattern of Cu-Kα radiation of the B-type crystal of the compound of formula (II). [Diagram 5] 1 is a DSC pattern of the B-type crystals of the compound of formula (II). [Figure 6] 1 is a TGA pattern of the B-type crystals of the compound of formula (II). [Figure 7] 1 is an XRPD pattern of Cu-Kα radiation of the C-type crystal of the compound of formula (II). [Figure 8] 1 is a DSC pattern of the C-type crystals of the compound of formula (II). [Figure 9] 1 is a TGA pattern of the C-type crystals of the compound of formula (II). [Figure 10] 1 is an XRPD pattern of Cu-Kα radiation of the D-type crystal of the compound of formula (II). [Figure 11] 1 is a DSC pattern of the D-type crystals of the compound of formula (II). [Figure 12] 1 is a TGA pattern of the D-type crystals of the compound of formula (II). [Figure 13] 1 is an XRPD pattern of Cu-Kα radiation of E-type crystals of the compound of formula (III). [Figure 14] 1 is a DSC pattern of E-form crystals of the compound of formula (III). [Figure 15] 1 is a TGA pattern of E-type crystals of the compound of formula (III). [Figure 16]1 is an XRPD pattern of Cu-Kα radiation of F-type crystal of the compound of formula (III). [Figure 17] 1 is an XRPD pattern of Cu-Kα radiation of the G-type crystal of the compound of formula (III). [Figure 18] 1 is an XRPD pattern of Cu-Kα radiation of H-type crystal of the compound of formula (IV). [Figure 19] 1 is a DSC pattern of H-type crystals of the compound of formula (IV). [Figure 20] 1 is a TGA pattern of H-type crystals of the compound of formula (IV). [Figure 21] 1 is an XRPD pattern of Cu-Kα radiation of the I-type crystal of the compound of formula (IV). [Figure 22] 1 is an XRPD pattern of Cu-Kα radiation of J-type crystal of the compound of formula (IV). [Diagram 23] 1 is an XRPD pattern of Cu-Kα radiation of K-type crystal of the compound of formula (IV). [Figure 24] 1 is an XRPD pattern of Cu-Kα radiation of the L-type crystal of the compound of formula (V). [Diagram 25] 1 is an XRPD pattern of Cu-Kα radiation of M-type crystal of the compound of formula (V). [Figure 26] 1 is an XRPD pattern of Cu-Kα radiation of N-type crystal of the compound of formula (V). [Figure 27] 1 is an XRPD pattern of Cu-Kα radiation of O-type crystal of the compound of formula (VI). [Figure 28] 1 is an XRPD pattern of Cu-Kα radiation of P-type crystal of the compound of formula (VI). [Figure 29] 1 is an XRPD pattern of Cu-Kα radiation of the Q-type crystal of the compound of formula (VII). [Diagram 30] 1 is an XRPD pattern of Cu-Kα radiation of an R-type crystal of the compound of formula (VIII). [Diagram 31] 1 is an XRPD pattern of Cu-Kα radiation of the S-type crystal of the compound of formula (X). [Diagram 32] 1 is an XRPD pattern of Cu-Kα radiation of T-type crystal of the compound of formula (I). [Diagram 33] 1 is a DSC pattern of T-type crystals of the compound of formula (I). [Diagram 34] 1 is a TGA pattern of T-type crystals of the compound of formula (I). [Diagram 35] 1 is a DVS pattern of type A crystals of the compound of formula (II). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0224] In order to better understand the present invention, the present invention will be further described below with reference to specific examples, but the specific embodiments are not intended to limit the present invention.
[0225] Example 1: Preparation of A-type crystals of the compound of formula (II) [ka]
[0226] 15L of dioxane and 5L of water were added to the 50L reactor at 10-30°C. Compound 1 (1500g) and compound 2 (1335g) were added to the reactor in one portion while stirring. 1930g of potassium carbonate was added to the reactor in one portion while stirring. The atmosphere was purged with nitrogen for 10 minutes, then 100g of Pd(dppf)Cl2 was added to the reactor in one portion. The reaction was heated to an internal temperature of 88-90°C and continued to stir for 16 hours. 10L of the reaction solution was taken and added to the 50L reactor, 30L of water was added while stirring, and stirred at room temperature for 15 minutes. The remaining 10L was treated as above. Filtered under reduced pressure to obtain a filter cake. The filter cake was dried in an oven at 50°C for 48 hours. A metal scavenger (1000g), activated carbon (1000g), and magnesium sulfate (1000g) were added to a 50L reaction kettle and stirred at 60°C for 18 hours. The reaction solution was cooled to room temperature, then filtered through diatomaceous earth, and the filtrate was collected. The filtrate was concentrated to obtain a crude product. The reaction solution was filtered under reduced pressure while still hot, and the filter cake was eluted with anhydrous dioxane (4L x 2) to obtain a filtrate. The filtrate was spin-dried under reduced pressure at 40-50°C to obtain a residue. The concentrated crude product was transferred to a 50L reaction kettle, and 15L of n-heptane and 1.5L of dichloromethane were added, and the mixture was stirred at 25-35°C for 16 hours. The suspension in the reaction kettle was sent to a benchtop filter, suction filtered, the filter cake was eluted with n-heptane (2L x 2), the solid was collected, and the solid was spin-dried under reduced pressure at 40-50°C to obtain compound 3.
[0227] [ka]
[0228] Add 15L of N,N-dimethylformamide to a 50L reaction flask at 10-30°C, add compound 3 (1.5kg) and compound 4 (619.5g) to the reaction flask at once while stirring, add potassium carbonate (1.81kg) and Xphos (415.5g) to the reaction vessel at once while stirring, replace with nitrogen for 10 minutes, then add Pd2(dba)3 (399g) to the reaction vessel at once, heat the reaction to an internal temperature of 90-95°C (external temperature 100°C), continue stirring for 8 hours, track compound 3 ≦ 1% by HPLC, add 1kg of diatomaceous earth to a benchtop suction filter funnel, suction filter with a benchtop suction filter under reduced pressure, then add DMF (1L x 2) to wash, and collect the filtrate. The filtrate was concentrated under reduced pressure to about 1 / 3 of the reaction volume with an oil pump. The above concentrated liquid was added to a 50L reaction vessel, 3V of water was added, the pH was adjusted to 11-12 with 4M aqueous sodium hydroxide solution, and the mixture was suction filtered under reduced pressure. The filtrate was extracted with ethyl acetate (15L x 2) to remove some of the impurities, and the pH of the aqueous phase was adjusted to 5-6 with 3M aqueous hydrochloric acid solution to precipitate a large amount of yellow solid particles. The mixture was then filtered with a benchtop suction filter funnel to recover the solid, and the filter cake was dried in a vacuum oven at 50°C to obtain compound 5.
[0229] [ka]
[0230] At 20-30℃, add 11.5L of ethylene glycol dimethyl ether and 3.8L of water to a 50L reactor, add compound 5 (1150g) and compound 6 (676.15g) to the reaction flask all at once while stirring, add potassium carbonate (1183.60g) to the reaction flask all at once while stirring, replace with nitrogen for 10 minutes, then add Pd(dppf)Cl2 (208.87g) to the reaction flask all at once, heat the reaction to an internal temperature of 77-80℃, continue to stir for 16 hours, follow compound 5≦1% by HPLC, suction filter under reduced pressure with a benchtop suction filter funnel, then add 1L of ethylene glycol dimethyl ether to wash, and collect the filtrate. The filtrate was concentrated under reduced pressure by an oil pump to about 1 / 3 of the reaction volume, the above concentrated liquid was added to a 50L reaction kettle, 3V of water was added, the pH was adjusted to 13 with 4M aqueous sodium hydroxide solution, and then the pH was adjusted to 6 with 3M aqueous hydrochloric acid solution to precipitate a large amount of yellow-brown solid particles, which were then filtered through a benchtop suction filter funnel to recover the filter cake, and the filter cake was dried in an oven at 50°C to obtain a crude product.
[0231] Add 10.0L of DCM to the 50L reaction vessel at 20-30°C, add the crude product (1000g), DPPE (37.94g) and propylenediamine (81.11mL) to the reaction vessel at once while stirring, heat the reaction to an internal temperature of 40°C, continue to stir for 16 hours, suction filter under reduced pressure, then add DCM (500mL) to wash, and collect the filter cake. The above operation was repeated three times. Add 3.0L of THF to the 50L reaction flask at 10-30°C, add the filter cake to the reaction vessel while stirring, heat the reaction to an internal temperature of 60°C, continue to stir for 16 hours, suction filter under reduced pressure, then add 500mL of THF to wash, and collect the filter cake. The filter cake was dried in vacuum at 40-50°C. Add 5.0L DMF and 5.0L dioxane to the 50L reaction kettle at 10-30°C, add the crude product to the reaction kettle while stirring, heat the reaction to an internal temperature of 50°C, continue to stir for 16 hours, suction filter under reduced pressure, then add 500mL dioxane to wash, and collect the filter cake. Vacuum dry the filter cake at 40-50°C. Add 10.0L THF to the 50L reaction kettle at 10-30°C. Add the filter cake to the reaction flask while stirring, heat the reaction to an internal temperature of 60°C, continue to stir for 16 hours, suction filter under reduced pressure, then add 500mL THF to wash, and collect the filter cake. Vacuum dry the filter cake at 40-50°C to obtain the crude product. 20.0L of water was added to the 50L reactor at 10-30°C, the filter cake was added to the reactor while stirring, the pH was adjusted to 5-6, the reactor was heated to 40°C, and stirring was continued for 16 hours, suction filtered under reduced pressure, and then 2L of water was added to wash and collect the filter cake. The filter cake was dried in vacuum at 40-50°C to obtain the compound of formula (I). The compound of formula (I) was characterized as T-type crystals by XRPD. The XRPD pattern was shown in Figure 32, the DSC pattern in Figure 33, and the TGA pattern in Figure 34.
[0232] [ka]
[0233] The compound of formula (I) (740 g) was added to DMSO (7.4 L), methanesulfonic acid (155.41 g, 1.62 mol, 115.12 mL, 1.05 eq) was added to the reaction solution at 20-30 ° C., the reaction was stirred at 20-30 ° C. for 4 hours, 37 L of ethyl acetate was added to the reaction solution, the reaction solution was kept stirred for 16 hours, a large amount of solid was precipitated, filtered, the filter cake was washed with ethyl acetate (2 L × 2), the filter cake was spin-dried under reduced pressure at 40-50 ° C., and the A-type crystal of the compound of formula (II) was obtained. The XRPD pattern of the A-type crystal is shown in Figure 1, the DSC pattern is shown in Figure 2, and the TGA pattern is shown in Figure 3.
[0234] 1 H NMR (400MHz, DMSO-d6) δ 8.83 (d, J=4.0 Hz, 1H), 8.60 (s, 1H), 8.46 (s, 1H), 8.27 (s, 1H), 8.10-8.04 (m, 2H), 7.76 (s, 1H), 7.72 (d, J=4.0 Hz, 1H), 7.50-7.32 (m, 2H), 7.24 (s, 1H), 3.93 (s, 3H), 3.47 (s, 3H), 2.30(s, 3H).
[0235] Example 2: Preparation of B-type crystals of the compound of formula (II) 20 mg of the compound of formula (I) and methanesulfonic acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of acetone was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50° C. and dried under vacuum for 30 minutes to obtain B-type crystals of the compound of formula (II).
[0236] Preparation of C-type crystals of the compound of formula (II) 20 mg of the compound of formula (I) and methanesulfonic acid (1 eq) were weighed and added to each HPLC vial, and 0.5 mL of EtOH / HO (19:1, v / v) was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain C-type crystals of the compound of formula (II).
[0237] Preparation of D-type crystals of the compound of formula (II) 75g of the compound of formula (I) was added to DMSO (750mL), methanesulfonic acid (15g, 1eq) was added to the reaction solution at 20-30°C to dissolve and clarify the reaction solution, and the mixture was stirred for 4 hours. 1.5L of ethyl acetate was added to the reaction solution, stirred for 20 hours, solids were precipitated, filtered, the filter cake was washed with ethyl acetate (50mL x 2), and concentrated to dryness to obtain a crude product (about 45g). The crude product was added to ethanol (450mL), stirred for 24 hours at 20-30°C, filtered, the filter cake was washed with ethanol (10mL x 2), and the filter cake was spin-dried under reduced pressure at 40-50°C to obtain D-type crystals of the compound of formula (II).
[0238] 1 H NMR (400MHz, DMSO-d6) δ 11.07 (brs, 1H), 8.86 (d, J=4.0 Hz, 1H), 8.63 (s, 1H), 8.56 (s, 1H), 8.26 (s, 1H), 8.15 (s, 1H), 8.08-8.06 (m, 1H), 7.79-7.77 (m, 2H), 7.48-7.30 (m, 2H), 7.27 (s, 1H), 3.93 (s, 3H), 3.47 (s, 3H), 2.41(s, 3H).
[0239] Preparation of E-type crystals of the compound of formula (III) Weigh out 100 mg of the compound of formula (I) and add it to DMSO (1 mL). Add hydrochloric acid (20.51 mg, 208.12 μmol, 17.34 μL, purity 37%) to the reaction solution at 20-30 ° C. to react, stir at 20-30 ° C. for 24 hours, filter, wash the filter cake with ethyl acetate (1 mL × 2), spin-dry the filter cake under reduced pressure at 40-50 ° C. to obtain E-type crystals of the compound of formula (III). 1H NMR (400MHz, DMSO-d6) δ 11.04 (brs, 1H), 8.85 (d, J=4.0 Hz, 1H), 8.63 (s, 1H), 8.49 (s, 1H), 8.29 (s, 1H), 8.08-8.06 (m, 2H), 7.77-7.72 (m, 2H), 7.49-7.34 (m, 2H), 7.26 (s, 1H), 3.94 (s, 3H), 3.46 (s, 3H).
[0240] Preparation of F-type crystals of the compound of formula (III) 20 mg of the compound of formula (I) and 1 eq of hydrochloric acid were weighed and added to an HPLC vial, and 0.5 mL of EtOH / HO (19:1, v / v) was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain F-type crystals of the compound of formula (III).
[0241] Preparation of G-type crystals of the compound of formula (III) 100 mg of the compound of formula (I) was weighed and added to DMSO (1 mL). Hydrochloric acid (20.51 mg, 208.12 μmol, 17.34 μL, purity 37%) was added to the reaction solution at 20-30 ° C. to react, stirred at 20-30 ° C. for 24 hours, filtered, the filter cake was washed with ethyl acetate (1 mL × 2), and the filter cake was spin-dried under reduced pressure at 40-50 ° C. to obtain G-type crystals of the compound of formula (III).
[0242] Preparation of H-type crystals of the compound of formula (IV) 20 mg of the compound of formula (I) and sulfuric acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of ethanol was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain H-type crystals of the compound of formula (IV).
[0243] Preparation of Form I Crystals of Compound of Formula (IV) 20 mg of the compound of formula (I) and sulfuric acid (1 eq) were weighed and added to each HPLC vial, and 0.5 mL of EtOH / HO (19:1, v / v) was mixed and added. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain type I crystals of the compound of formula (IV).
[0244] Preparation of J-type crystals of the compound of formula (IV) 20 mg of the compound of formula (I) and sulfuric acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of tetrahydrofuran was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain J-type crystals of the compound of formula (IV).
[0245] Preparation of K-type crystals of the compound of formula (IV) Weigh out 100 mg of the compound of formula (I) and add it to DMSO (1 mL). Add sulfuric acid (20.41 mg, 208.12 μmol, 11.09 μL, 1 eq) to the reaction solution at 20-30 ° C., stir the reaction solution at 20-30 ° C. for 20 hours, add 2 mL of ethyl acetate to the reaction solution, continue to stir the reaction solution for 20 hours, filter, wash the filter cake with ethyl acetate (1 mL × 2), spin-dry the filter cake under reduced pressure at 40-50 ° C., and obtain K-type crystals of the compound of formula (IV).
[0246] 1 H NMR (400MHz, DMSO-d6) δ 11.05 (brs, 1H), 8.85 (d, J=4.0 Hz, 1H), 8.63 (s, 1H), 8.53 (s, 1H), 8.30 (s, 1H), 8.09-8.06 (m, 2H), 7.77-7.75 (m, 2H), 7.49-7.33 (m, 2H), 7.24 (s, 1H), 3.94 (s, 3H), 3.46 (s, 3H).
[0247] Preparation of L-type crystals of the compound of formula (V) 20 mg of the compound of formula (I) and phosphoric acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of ethanol was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain L-type crystals of the compound of formula (V).
[0248] 1 H NMR (400MHz, DMSO-d6) δ 8.84 (d, J=4.0 Hz, 1H), 8.63 (s, 1H), 8.47 (s, 1H), 8.28 (s, 1H), 8.09-8.02 (m, 2H), 7.77-7.70 (m, 2H), 7.50-7.45 (m, 3H), 7.36 (t, J=4.0 Hz, 1H), 7.24 (s, 1H), 7.11 (d, J=4.0 Hz, 2H), 3.94 (s, 3H), 2.29 (s, 3H).
[0249] Preparation of M-type crystals of the compound of formula (V) 20 mg of the compound of formula (I) and phosphoric acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of EtOH / HO (19:1, v / v) was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain M-type crystals of the compound of formula (V).
[0250] Preparation of N-type crystals of the compound of formula (V) 20 mg of the compound of formula (I) and phosphoric acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of tetrahydrofuran was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50° C. and dried under vacuum for 30 minutes to obtain N-type crystals of the compound of formula (V).
[0251] Preparation of O-type crystals of the compound of formula (VI) 20 mg of the compound of formula (I) and p-toluenesulfonic acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of acetone was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain O-type crystals of the compound of formula (VI).
[0252] Preparation of P-type crystals of the compound of formula (VI) 20 mg of the compound of formula (I) and p-toluenesulfonic acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of tetrahydrofuran was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50° C. and dried under vacuum for 30 minutes to obtain P-type crystals of the compound of formula (VI).
[0253] Preparation of Q-type crystals of the compound of formula (VII) 20 mg of the compound of formula (I) and oxalic acid (1 eq) were weighed and added to an HPLC vial, respectively, and 0.5 mL of EtOH / HO (19:1, v / v) was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain Q-type crystals of the compound of formula (VII).
[0254] Preparation of R-type crystals of the compound of formula (VIII) 20 mg of the compound of formula (I) and maleic acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of acetone was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain R-type crystals of the compound of formula (VIII).
[0255] 1 H NMR (400MHz, DMSO-d6) δ 8.73 (d, J=4.0 Hz, 1H), 8.47 (s, 1H), 8.21 (s, 2H), 8.09-8.03 (m, 2H), 7.99 (s, 1H), 7.75 (s, 1H), 7.49-7.30 (m, 3H), 7.23 (s, 1H), 6.22 (s, 2H), 3.92 (s, 3H), 3.46 (s, 3H).
[0256] Preparation of S-type crystals of the compound of formula (X) 20 mg of the compound of formula (I) and tartaric acid (1 eq) were weighed and added to an HPLC vial, and 0.5 mL of acetone was added and mixed. The mixture was stirred at room temperature for 4 days, centrifuged, and the solid was transferred to 50°C and dried under vacuum for 30 minutes to obtain S-form crystals of the compound of formula (X).
[0257] 1 H NMR (400MHz, DMSO-d6) δ 8.68 (d, J=4.0 Hz, 1H), 8.47 (s, 1H), 8.13 (s, 1H), 8.09-8.02 (m, 2H), 7.95 (s, 1H), 7.77 (s, 1H), 7.49-7.33 (m, 3H), 7.24 (s, 1H), 4.32 (s, 3H), 3.94 (s, 3H).
[0258] Experimental Example 3: Hygroscopicity study of the A-type crystals of the compound of formula (II) Experimental materials: SMS Intrinsic Dynamic Water Vapor Sorption Apparatus
[0259] Experimental Method: 10-30 mg of type A crystals of the compound of formula (II) are taken and placed on a DVS sample tray for testing.
[0260] Test Results: The DVS pattern of the A-type crystals of the compound of formula (II) is shown in FIG. 35, with ΔW=1.708%.
[0261] Test conclusion: The A-type crystals of the compound of formula (II) show a hygroscopic weight increase of 1.708% at 25° C. and 80% RH.
[0262] Experimental Example 4: Stability data of the A-type crystals of the compound of formula (II) Tested under conditions of high temperature, high humidity and light, samples were placed in an open clean weighing bottle and spread into a thin layer of ≦5 mm, and three samples (1.1 g / part) were weighed in parallel at each condition time point, and the prepared samples were placed under each condition and samples were taken and analyzed at each time point.
[0263] Accelerated stability and long-term stability tests were conducted by placing samples in two-layer pharmaceutical low-density polyethylene bags, sealing each layer of the pharmaceutical low-density polyethylene bag with a buckle, and then placing the two-layer low-density polyethylene bag in an aluminum foil bag and heat sealing it. Six samples (1.1 g / part) were weighed in parallel at each time point, and the prepared samples were placed under each condition, and samples were taken and analyzed at each time point.
[0264] The A-type crystals of compound of formula (II) were subjected to the following conditions, and samples were taken at different time points to detect the physical properties, and the content and total impurities were analyzed by HPLC. The study conditions and test items are shown in Table 21 below.
[0265] [Table 21]
[0266] Experimental conclusion: Form A crystal of compound of formula (II) has good stability.
[0267] Biological Test Data:
[0268] Experimental Example 1: Study on the inhibitory effect of the A-type crystal of the compound of formula (II) on cell proliferation Objective of the experiment:
[0269] The compound of the present invention can target and inhibit FGFR and VEGFR pathways, and inhibit tumor cell proliferation by inhibiting VEGF / VEGFR, FGF / FGFR signaling pathways.In this experiment, human non-small cell lung cancer cells NCI-H1581 with high FGFR1 expression, gastric cancer cells SNU-16 with high FGFR2 expression, and human bladder cancer cells RT112 / 84 with high FGFR3 expression are selected, and the inhibitory effect of the compound of the present invention on cell proliferation is studied by detecting the effect of the compound of the present invention on the in vitro cell viability in tumor cell lines NCI-H1581, SNU-16, and RT-112 / 84.
[0270] Experimental methods and procedures:
[0271] cell culture The tumor cell lines were cultured in an incubator at 37° C. and 5% CO2 under the culture conditions shown in Table 22. They were passaged periodically, and cells in the logarithmic growth phase were harvested for plating.
[0272] [Table 22-1]
[0273] Cell plating (1) Cells were stained with trypan blue and viable cells were counted. (2) The cell concentration was adjusted to an appropriate concentration.
[0274] [Table 22-2]
[0275] (3) 90 μL of the cell suspension was added to each well of the culture plate, and culture medium without cells was added to blank control wells. (4) The culture plate was incubated overnight in an incubator at 37°C, 5% CO2, and 100% relative humidity.
[0276] 2. Preparation of 10X Compound Working Solutions and Compound-treated Cells
[0277] (1) Preparation of 10X compound working solution: 78 μL of cell culture medium was added to a V-bottom 96-well plate, and 2 μL of compound was aspirated from a 400X compound storage plate and added to the cell culture medium in the 96-well plate. 2 μL of DMSO was added to the vehicle control and blank control. After compound or DMSO was added, the mixture was mixed well by blowing with a multichannel pipette. (2) Dosing: 10 μL of 10X compound working solution was added to cell culture plates. 10 μL of DMSO-cell culture medium mixture was added to vehicle control and blank control. The final concentration of DMSO was 0.25%. (3) The 96-well plate was returned to the incubator and cultured for 3 days before testing.
[0278] CellTiter-Glo Luminescent Cell Viability Assay The following procedure was performed according to the instructions of the Promega CellTiter-Glo Luminescent Cell Viability Assay Kit (Promega-G7573).
[0279] (1) CellTiter-Glo buffer was dissolved and allowed to stand at room temperature. (2) The CellTiter-Glo substrate was allowed to warm to room temperature. (3) A CellTiter-Glo working solution was prepared by adding CellTiter-Glo buffer to a vial of CellTiter-Glo substrate to dissolve the substrate. (4) Gently vortex to dissolve completely. (5) The cell culture plate was removed and left for 30 minutes to equilibrate to room temperature. (6) 50 μL (equal to half the volume of cell culture medium in each well) of CellTiter-Glo working solution was added to each well. The cell culture plate was wrapped in aluminum foil to block light. (7) To induce cell lysis, the culture plate was shaken on an orbital shaker for 2 minutes. (8) To stabilize the luminescence signal, the culture plate was left at room temperature for 10 minutes. (9) Luminescent signals were detected using a 2104 EnVision plate reader. Data Analysis:
[0280] Calculate the inhibition rate (IR) of the test compounds using the following formula: IR(%)=(1-(RLU compound-RLU blank control) / (RLU vehicle control-RLU blank control))*100%. Calculate the inhibition rate of different concentrations of compounds in Excel and plot the inhibition curves using GraphPad Prism software to calculate the minimum inhibition rate, maximum inhibition rate, IC 50 Related parameters such as IC were calculated using the following formula: 50 was calculated.
[0281] Y=Minimum suppression rate + (Maximum suppression rate - Minimum suppression rate) / (1+10^((LogIC 50 -X)*HillSlope)) X:log(concentration) Y: Response value, whose value is negatively correlated with X HillSlope:Slope coefficient
[0282] Experimental results: see Table 23.
[0283] [Table 23]
[0284] Experimental conclusion: Form A crystal of the compound of formula (II) exhibits certain anti-cell proliferation activity against three tumor cell lines with high expression of FGFR.
[0285] Experimental Example 2: In vitro BaF3 cell line activity of the A-type crystals of the compound of formula (II)
[0286] Objective of the experiment: In this experiment, modified cells expressing VEGFR (Ba / F3-TEL-FLT1(VEGFR1), Ba / F3-TEL-FLT4(VEGFR3), Ba / F3-TEL-VEGFR2) were selected to evaluate the in vitro proliferation inhibitory effect of the A-type crystals of the compound of formula (II) on the BaF3 cell line.
[0287] Experimental methods and procedures: Preparation of a solution of 1000x crystals of type A of the compound of formula (II)
[0288] The A-type crystals of compound of formula (II) were dissolved in DMSO to prepare a 10 mM mother solution, which was then diluted 4-fold to 10.0000 mM, 2.5000 mM, 0.6250 mM, 0.1563 mM, 0.0391 mM, 0.0098 mM, 0.0024 mM, 0.0006 mM, and 0.0002 mM, and stored in a 96-well drug plate (Beaver, Suzhou), for a total of nine concentration gradients, and the same volume of DMSO solvent was used as a negative control.
[0289] 1. A cell suspension in the logarithmic growth phase was harvested and inoculated into a 96-well white cell culture plate (Corning 3917, NY, USA) at a volume of 95 μL per well (2000 cells / well).
[0290] 2. The diluted medium-compound mixture was added respectively, the volume of each well was 5 μL, and the final concentration of DMSO in Ba / F3-TEL-FLT1(VEGFR1), Ba / F3-TEL-FLT4(VEGFR3), Ba / F3-TEL-VEGFR2 cells was 0.1%.
[0291] [Table 24]
[0292] 3. Incubate in a 37℃, 5% CO2 incubator for 72 hours. 4. The proliferation inhibitory activity of the compounds and data analysis by the CellTiter-Glo method were the same as in Experimental Example 1.
[0293] Results of the experiment: see Table 25. [Table 25]
[0294] Experimental conclusion: In modified cells expressing VEGFR (Ba / F3-TEL-FLT1(VEGFR1), Ba / F3-TEL-FLT4(VEGFR3), Ba / F3-TEL-VEGFR2), the A-type crystals of the compound of formula (II) exhibit certain anti-cell proliferation activity, and Ba / F3-TEL-VEGFR2 exhibits strong anti-proliferative activity.
[0295] Experimental Example 3: Pharmacokinetic evaluation of the A-type crystals of the compound of formula (II)
[0296] Aim of the experiment: To evaluate the animal oral absorption of crystalline form A of the compound of formula (II) after a single intravenous injection and intragastric administration in SD rats. Experimental materials: SD rats, EDTA-K2
[0297] Experimental procedure:
[0298] Experimental procedure: A clear solution of the A-type crystals of the compound of formula (II) at a concentration of 5 mg / mL in 5% DMSO / 10% Solutol / 85% water was intravenously injected into male and female SD rats (fasted overnight, 7-11 weeks old) at a dose of 10 mg / kg.
[0299] 1 mg / mL, 3 mg / mL, and 10 mg / mL of the A-type crystals of the compound of formula (II) in 5% DMSO / 10% Kolliphor HS15 / 85% (0.2% (v / v) Tween 80 aqueous solution) were administered intragastrically to male and female SD rats (overnight fasted, 7-11 weeks old) at doses of 10 mg / kg, 30 mg / kg, and 100 mg / kg. Approximately 0.2 mL of blood was collected from the jugular vein of all four animals at 0.25, 0.5, 1.0, 2.0, 4.0, 8.0, and 24 hours (IV group increased by 0.083 hours) after administration, placed in an anticoagulant tube with EDTA-K2, and the plasma was centrifuged. Blood drug concentrations were measured by LC-MS / MS method, and relevant pharmacokinetic parameters were calculated by the noncompartmental model linear-logarithmic trapezoidal method using WinNonlin® Version 6.3 (Pharsight, Mountain View, CA) pharmacokinetic software.
[0300] Test Results:
[0301] After a single intravenous injection of 1 mg / kg of crystalline form A of the compound of formula (II) into male and female SD rats, the plasma clearance (Cl) was 8.78 and 7.03 mL / min / kg, respectively, and the steady-state distribution volume (Vd ss ) were 0.419 and 0.366 L / kg, and the elimination half-life (T 1 / 2 ) were 0.675 and 0.765 h, respectively, and the areas under the plasma concentration-time curve from 0 to the last quantifiable time point (AUC 0-last ) values are 3980 and 4930 nM h, respectively.
[0302] The total body exposure (AUC 0-last and C0), there are no significant gender differences.
[0303] After a single intragastric administration of 10, 30 and 100 mg / kg of the A-type crystals of the compound of formula (II) to male SD rats, the peak concentrations (C max ) were 3780, 16700 and 19900 nM, respectively, and the peak times (T max ) appear at 0.500, 1.00, and 0.833 h after administration, respectively. AUC 0-last were 7150, 38200, and 113000 nM·h, respectively. The bioavailability of the drug in the 10 mg / kg intragastric administration group was 18.0%.
[0304] After single intragastric administration of 10, 30 and 100 mg / kg of the A-type crystals of the compound of formula (II) to female SD rats, the peak concentrations (C max ) were 9170, 24500 and 27400 nM, respectively, and the peak times (T max ) appear at 0.667, 1.00, and 0.500 h after administration, respectively. AUC 0-last were 24,800, 65,600, and 125,000 nM·h, respectively. The bioavailability of the drug in the 10 mg / kg intragastric administration group was 50.3%.
[0305] At intragastric doses of 30 and 100 mg / kg, the systemic exposure (AUC 0-last and C. max ) there is no significant gender difference.
[0306] Conclusion: Crystalline Form A of the compound of formula (II) has low clearance, acceptable oral bioavailability, and good druggability in rat species.
[0307] Experimental Example 4: Pharmacokinetic study of the compounds of the present invention in rats Experimental animals: SD rats (fasted overnight, 7-11 weeks old)
[0308] Experimental procedure:
[0309] Experimental procedure: A clear solution of the compound of the present invention or its crystals at a concentration of 10 mg / mL in 5% DMSO / 10% Solutol / 85% water was intravenously injected into male SD rats (fasted overnight, 7 to 11 weeks old) at a dose of 100 mg / kg.
[0310] The compound of the present invention or its crystals in 5% DMSO / 10% Kolliphor HS15 / 85% (0.2% (v / v) Tween 80 aqueous solution) at 10 mg / mL was intragastrically administered to male SD rats (fasted overnight, 7-11 weeks old) at a dose of 100 mg / kg. Approximately 0.2 mL of blood was collected from the jugular vein of each of the three groups of animals at 0.25, 0.5, 1.0, 2.0, 4.0, 8.0 and 24 h after administration, and placed in an anticoagulant tube containing EDTA-K2, and the plasma was centrifuged. Blood drug concentrations were measured by LC-MS / MS method, and the relevant pharmacokinetic parameters were calculated by the non-compartmental model linear logarithmic trapezoidal method using WinNonlin® Version 6.3 (Pharsight, Mountain View, CA) pharmacokinetic software.
[0311] Test Results:
[0312] [Table 26-1]
[0313] Experimental conclusion: At the same dose, crystalline form D of compound of formula (II) shows higher exposure and Cmax than crystalline form E of compound of formula (III) and compound of formula (I).
[0314] Experimental Example 5: In vivo antitumor activity test of the A-type crystals of the compound of formula (II) in animal tumor models
[0315] Purpose of the experiment: In this study, the antitumor efficacy of crystalline Form A of the compound of formula (II) is evaluated using a Renca subcutaneous xenograft tumor nude mouse model.
[0316] Experimental animals: Female Balb / c mice (6-8 weeks old)
[0317] Experimental Method: cell culture
[0318] Mouse renal carcinoma Renca cells (ATCC-CRL-2947) were cultured on an in vitro wall, and the culture conditions were RPMI 1640 medium supplemented with 10% fetal bovine serum, 0.1 mM non-essential amino acids, 1 mM sodium pyruvate, 2 mM glutamine, 100 U / mL penicillin, and 100 μg / mL streptomycin, and cultured in an incubator at 37 °C and 5% CO2. Conventional passage was performed twice a week. When the cells reached 80%-90% saturation and the number reached the required amount, the cells were collected, counted, and inoculated.
[0319] cell inoculation 0.1mL (1×10 5 Renca cells (1000 cells) were subcutaneously inoculated into the dorsal side of the right upper limb of each mouse, and the average tumor volume was approximately 50–80 mm 3 When this reached the target age, the animals were divided into groups and administered the drug.
[0320] Tumor measurements and experimental indices Tumor diameters were measured twice a week with a caliper. Tumor volume was calculated using the formula: V = 0.5a × b 2 where a and b represent the long and short diameters of the tumor, respectively.
[0321] The antitumor effect of the compound is evaluated by TGI (%) or relative tumor proliferation rate T / C (%). Relative tumor proliferation rate T / C (%) = T RTV / C RTV ×100%(T RTV : Mean RTV of treatment group, C RTV Relative tumor volume (RTV) was calculated based on the tumor measurement results, and the formula was RTV = V t / V0, where V0 is the tumor volume measured at the time of group dosing (i.e., D0), and V t is the tumor volume at a particular measurement in the corresponding mouse, and T RTV and C RTV is data for the same day.
[0322] TGI (%) reflects the tumor growth inhibition rate: TGI (%) = [(1-(mean tumor volume at the end of treatment for a particular treatment group-mean tumor volume at the start of treatment for that treatment group) / (mean tumor volume at the end of treatment for the vehicle control group-mean tumor volume at the start of treatment for the vehicle control group)] x 100%.
[0323] Statistical analysis was performed based on the RTV data at the end of the experiment using SPSS software. Comparisons between two groups were analyzed using T-tests, and comparisons between three or more groups were analyzed using one-way ANOVA. If the variances were equal (no significant difference in F-values), Tukey's test was used to analyze, and if the variances were unequal (if there was a significant difference in F-values), the Games-Howell test was used to detect the difference. p<0.05 was considered to be significant.
[0324] Test Results: The group administered with the A-type crystal of the compound of formula (II) (100 mg / kg) had a clear effect of inhibiting tumor growth, and the difference was significant (p=0.031) compared with the solvent control group.
[0325] [Table 26-2]
[0326] Note: QD: once daily administration, TGI%: tumor growth inhibition rate
[0327] Experimental conclusion: Form A crystal of compound of formula (II) shows excellent tumor inhibitory effect in Renca xenograft tumor model.
Claims
1. A compound represented by formula (II): 【Chemistry 1】
2. A type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.65±0.20°, 17.70±0.20°, and 24.02±0.20°, and at a radiation source of Cu Kα. 【Chemistry 2】
3. The A-type crystal according to claim 2, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.65±0.20°, 16.84±0.20°, 17.70±0.20°, 20.10±0.20°, 20.91±0.20°, and 24.02±0.20°, with a radiation source of Cu Kα.
4. The A-type crystal according to claim 3, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.65±0.20°, 16.84±0.20°, 17.70±0.20°, 20.10±0.20°, 20.91±0.20°, 24.02±0.20°, 24.98±0.20°, and 26.60±0.20°, radiation source: Cu Kα.
5. The A-type crystal according to claim 4, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.649°, 12.713°, 16.841°, 17.695°, 20.100°, 20.912°, 24.018°, 24.976°, 26.599°, and 28.076°, with a radiation source of Cu Kα.
6. 6. The A-type crystal of claim 5, having an XRPD pattern as shown in Table 1 below. 【Table 1】 Radiation source: Cu Kα
7. The differential scanning calorimetry curve shows one endothermic peak at 283.9±3.0° C. The A-type crystal according to any one of claims 2 to 6.
8. The A-type crystal according to any one of claims 2 to 6, wherein the thermogravimetric analysis curve shows a weight loss of 0.955% at 200.0±3.0°C.
9. A B-type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.75±0.20°, 9.94±0.20°, and 23.94±0.20°, and a radiation source: Cu Kα. 【Chemistry 3】
10. The B-type crystal according to claim 9, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.75±0.20°, 9.94±0.20°, 11.70±0.20°, 17.52±0.20°, 20.36±0.20°, and 23.94±0.20°, with a radiation source of Cu Kα. 【Chemistry 4】
11. The B-type crystal according to claim 10, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.75±0.20°, 9.94±0.20°, 11.70±0.20°, 14.38±0.20°, 17.52±0.20°, 18.95±0.20°, 20.36±0.20°, and 23.94±0.20°, radiation source: Cu Kα.
12. The B-type crystal according to claim 11, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.75°, 9.94°, 11.70°, 13.62°, 14.38°, 15.47°, 17.52°, 18.95°, 20.36°, 23.94°, 25.34°, 25.46°, 26.93°, 28.79°, radiation source: Cu Kα.
13. 13. The B-type crystal of claim 12, having an XRPD pattern as shown in Table 2 below. 【Table 2】 Radiation source: Cu Kα
14. The B-type crystal according to any one of claims 9 to 13, wherein the differential scanning calorimetry curve shows the onset of one endothermic peak at 57.40±3.0°C and 296.86±3.0°C, respectively.
15. The B-type crystal according to any one of claims 9 to 13, wherein the thermogravimetric analysis curve shows a weight loss of 10.53% at 150.0±3.0°C.
16. A D-type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 10.78±0.20°, 13.64±0.20°, and 16.66±0.20°, and a radiation source: Cu Kα. 【Chemistry 5】
17. The D-type crystal according to claim 16, having a powder X-ray diffraction pattern having characteristic diffraction peaks at the following 2θ angles: 10.78±0.20°, 13.64±0.20°, 16.66±0.20°, 19.63±0.20°, 21.13±0.20°, and 25.40±0.20°, radiation source: Cu Kα.
18. The D-type crystal according to claim 17, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 5.51±0.20°, 8.73±0.20°, 10.78±0.20°, 13.64±0.20°, 16.66±0.20°, 19.63±0.20°, 21.13±0.20°, and 25.40±0.20°, radiation source: Cu Kα.
19. Powder X-ray diffraction pattern at the following 2θ angles: 5.51°, 8.10°, 8.73°, 10.78°, 12.64°, 13.64°, 14.47°, 14.92°, 15.80°, 16.66°, 17.47°, 19.03°, 19.63°, 21.13°, 21.69°, 22.02°, 22.20°, 23.84°, 24.31°, 25.40°, 25.93°, 26.28°, 26.84°, 27.41°, 27.93°, 29.10°, 30.01°, 30.78°, 32.16°, 32.78°, 33.57°, 38.41°; radiation source: Cu The D-type crystal according to claim 18, having a characteristic diffraction peak in Kα.
20. 20. The D-type crystal of claim 19, having an XRPD pattern as shown in Table 4 below. 【Table 3】 Radiation source: Cu Kα
21. The D-type crystal according to any one of claims 16 to 20, wherein the differential scanning calorimetry curve shows the onset of one endothermic peak at 27.1±3.0°C and 298.8±3.0°C, respectively.
22. The D-type crystal according to any one of claims 16 to 20, wherein the thermogravimetric analysis curve shows a weight loss of 3.15% at 150.0±3.0°C.
23. Use of the compound according to claim 1, or the A-type crystal according to any one of claims 2 to 8, the B-type crystal according to any one of claims 9 to 15, or the D-type crystal according to any one of claims 16 to 22 in the manufacture of a drug for treating a disease associated with an FGFR / VEGFR dikinase inhibitor.
24. The use according to claim 23, characterized in that the drug related to the FGFR / VEGFR dikinase inhibitor is a drug for treating solid tumors.
Citation Information
Patent Citations
Bicyclic heterocyclic compounds as FGFR inhibitors
JP2010513447A
New regulations for compounds
JP2010513448A
Bicyclic and heterocyclic compounds as protein tyrosine kinase inhibitors
JP2011500544A
Bicyclic and heterocyclic compounds as protein tyrosine kinase inhibitors
JP2011500545A
Imidazopyridine derivatives as inhibitors of receptor tyrosine kinases
JP2011522866A
